2004
DOI: 10.1103/physrevlett.93.198001
|View full text |Cite
|
Sign up to set email alerts
|

Intruders in the Dust: Air-Driven Granular Size Separation

Abstract: Using MRI and high-speed video we investigate the motion of a large intruder particle inside a vertically shaken bed of smaller particles. We find a pronounced, non-monotonic density dependence, with both light and heavy intruders moving faster than those whose density is approximately that of the granular bed. For light intruders, we furthermore observe either rising or sinking behavior, depending on intruder starting height, boundary condition and interstitial gas pressure. We map out the phase boundary deli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 21 publications
2
42
3
Order By: Relevance
“…When an object impacts on a bed of fine, loose grains, it is quickly engulfed and a surprisingly vigorous jet shoots upward from the surface of the sand [1][2][3][4], similar to what happens in a liquid [5][6][7]. Royer et al [4] found a granular jet created at reduced ambient pressure to be smaller than at atmospheric pressure, highlighting the relevant role that interstitial air plays in systems with very small grains (<100 m) [8][9][10].…”
mentioning
confidence: 99%
“…When an object impacts on a bed of fine, loose grains, it is quickly engulfed and a surprisingly vigorous jet shoots upward from the surface of the sand [1][2][3][4], similar to what happens in a liquid [5][6][7]. Royer et al [4] found a granular jet created at reduced ambient pressure to be smaller than at atmospheric pressure, highlighting the relevant role that interstitial air plays in systems with very small grains (<100 m) [8][9][10].…”
mentioning
confidence: 99%
“…Other mechanisms from topological considerations have also been proposed, such as arching (Duran et al, 1993) and "void filling" beneath large particles (Rosato et al, 2002). In addition to these mechanisms, air-driven segregation has also been found to be important in the case of very fine particles (Mobius et al, 2001;Burtally et al, 2002;Mobius et al, 2004). Despite the variety of mechanisms proposed, many important details of the microscopic dynamics driving the segregation remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently gained more attention in fundamental experimental (Mobius et al, 2001;Breu et d., 2003;NahmadMolinari et al, 2003;Huerta and Ruiz-SuGrez, 2004b;Mobius et al, 2004) and theoretical studies (Rosato et al, 1987;Shishodia and Wassgren, 2001;Hong et al, 2001;Trujillo et al, 2003). Efforts have been made in these studies to explain segregation from the non-equilibrium, dissipative nature of granular material and to establish hydrodynamics models for segregation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Mg, 64.75.+g, 05.50.+q In the last decades a great attention has been devoted to the study of the problem of vertically shaken granular mixtures under gravity. It was observed that such systems depending on the control parameters can mix or segregate their components spontaneously according to a mechanism which is still largely unclear, although of deep practical and conceptual relevance [1,2]. Rosato et al [3] showed that large grains surrounded by a sea of smaller ones rise to the top when subjected to vertical shaking.…”
mentioning
confidence: 99%